Los valores del juego de parada óptima para medias aritméticas de variables de Bernoulli - Lobo, Jaime (2003)
We study optimal stopping problems for generalized averages of identically distributed Bernoulli variables, taking values in the set D = {d0, d1}. We obtain a recurrent formula in the finite horizon case, which gives the value of the game in terms of associated problems of smaller horizon. This allows us to create algorithms for computing the value of the game, as well as the optimal stopping time in these cases. Moreover, we present a series of aplicattions to the study of properties of the value as a function of the parameters.